A review on the development of elemental and codoped TiO2 photocatalysts for enhanced dye degradation under UV–vis irradiation. (June 2022) - Nur, Alam S.M.; Sultana, Marzia; Mondal, Atol; Islam, Sumon; Robel, Fataha Nur; Islam, Aminul; Sumi, Mst. Sumaia Aktar
Abstract: Dye-contaminated water is a global problem due to its negative impact on human health and the aquatic environment. Photocatalysis is the most promising technique for dye pollution remediation, and TiO2 is the prime choice photocatalyst due to its complete removal capacity of dyes from wastewater. However, the low quantum efficiency of TiO2 under solar radiation limits its commercialization in the treatment of dye-containing wastewater. Therefore, extensive research has been conducted to increase the quantum efficiency of TiO2 through doping and morphological modifications to enhance the dye degradation efficiency under UV–Vis irradiation. Different doped TiO2 can be prepared by sol-gel, hydrothermal, solvothermal methods, etc. The photodegradation activity of doped TiO2 depends on the type of dopant and its concentration, preparation methods, morphology, and nature of dye molecules. Metal and nonmetal codoped TiO2 exhibited excellent dye degradation activity under UV–Vis irradiation. However, the photocatalytic efficiency decreased above the optimum dopants concentration. This study introduces the dye degradation performance of different elemental and codoped TiO2 photocatalysts under UV–Vis irradiation. In addition, it provides comprehensive information, a detailed survey, and a discussion on doped and codoped TiO2 photocatalysts. This study also provides reasons for the enhanced photodegradation activity of doped TiO2 . Finally, this review also recommended insightful future research directions to overcome the limitations of doped TiO2 photocatalysts in the treatment of dye-contaminated wastewater. Graphical abstract: Unlabelled Image